Facile synthesis of silver/silver thiocyanate (Ag@AgSCN) plasmonic nanostructures with enhanced photocatalytic performance - Zhao, Xinfu; Chen, Dairong; Qayum, Abdul; Chen, Bo; Jiao, Xiuling (Beilstein Journal of Nanotechnology, 2017)
A nanostructured plasmonic photocatalyst, silver/silver thiocyanate (Ag@AgSCN), has been prepared by a simple precipitation method followed by UV-light-induced reduction. The ratio of Ag to silver thiocyanate (AgSCN) can be controlled by simply adjusting the photo-induced reduction time. The formation mechanism of the product was investigated based on the time-dependent experiments. Further experiments indicated that the prepared Ag@AgSCN nanostructures with an atomic ratio of Ag/AgSCN = 0.0463 exhibited high photocatalytic activity and long-term stability for the degradation of oxytetracycline (84%) under visible-light irradiation. In addition to the microstructure and high specific surface area, the enhanced photocatalytic activity was mainly caused by the surface plasmon resonance of Ag nanoparticles, and the high stability of AgSCN resulted in the long-term stability of the photocatalyst product.
Keywords: Ag@AgSCN; degradation of oxytetracycline; plasmonic photocatalyst; stability